Studi Living Qur’an: Tradisi Semaan Al-Qur’an dan Dzikrul Ghafilin Jumat Kliwon pada Majelis Moloekatan Gus Miek di Desa Banjarsari, Bandarkedungmulyo, Jombang - Riza Nur laili; M. Fajrul Munawir (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2024)
This research was conducted based This research was conducted based on the author's interest in the phenomenon of semaan al-Qur'an and dzikrul ghafilin Friday kliwon at Gus Miek's moloekatan assembly, in Banjarsari Village, Bandarkedungmulyo, Jombang. The activities that have been carried out in recent years, appear to bring changes to the people of Banjarsari Village in particular, both in terms of economy, health, and religiously the community tends to increase. This research aims to find out how the implementation process and the meaning in accordance with the expression of the congregation in this tradition. This research uses emic ethnography method through Living Qur'an research with qualitative research type, the author also uses sociology of knowledge theory offered by Karl Mannheim. Data collection techniques, namely going directly to the field to make observations, interviews, and documentation. The results of this study are divided into two: First, it is held after the Fajr congregation until it is completed at night. The Qur'an is recited by the huffadz and listened to by the amaah. After khatam, continue mauidzoh hasanah by religious leaders, practice dzikrul ghafilin led by Gus thuba (Gus Miek's grandson), and closing prayer. Second, there are three meanings of tradition: objective meaning, improving friendship, the quality of worship, honoring the Prophet Muhammad saw, and the struggle of the leader of the village. Expressive meaning, seeking tranquility, filling leisure time, obtaining blessings. Documentary meaning, creating harmony, helping the seller's economy, also forming physical and spiritual health in each person.